2013
DOI: 10.1007/978-3-642-40480-1_30
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Supported Work in Partially Distributed and Co-located Teams: The Influence of Mood Feedback

Abstract: Abstract. This article examines the influence of mood feedback on different outcomes of teamwork in two different collaborative work environments. Employing a 2 x 2 between-subjects design, mood feedback (present vs. not present) and communication mode (face-to-face vs. video conferencing) were manipulated experimentally. We used a newly developed collaborative communication environment, called EmotiBoard, which is a large vertical interactive screen, with which team members can interact in a face-to-face disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Even though haptic systems can reduce sadness emotion and general negative mood significantly in remote interaction [12], they are more intrusive and less easy to use compared to a visual feedback display. For example, Sánchez et al have shown that it is possible to improve existing functionality of an instant messaging system for conveying emotion, as we did in a preliminary study for videoconferencing [5].…”
Section: Related Workmentioning
confidence: 82%
See 2 more Smart Citations
“…Even though haptic systems can reduce sadness emotion and general negative mood significantly in remote interaction [12], they are more intrusive and less easy to use compared to a visual feedback display. For example, Sánchez et al have shown that it is possible to improve existing functionality of an instant messaging system for conveying emotion, as we did in a preliminary study for videoconferencing [5].…”
Section: Related Workmentioning
confidence: 82%
“…Several strategies can be used for enhancing remote interaction through an emotion feedback, using different communication medium, e.g., visual displays [5], [10], taste and smell [11], or touch [12]. Even though haptic systems can reduce sadness emotion and general negative mood significantly in remote interaction [12], they are more intrusive and less easy to use compared to a visual feedback display.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to our knowledge, more attention should be paid on understanding the role of affective and social factors when learning collaboratively online, and there is still a need for further development of methodological approaches. The Self-Assessment Manikins (SAM) (Bradley, 1994) is usually used to evaluate the influence of an emotion representation as a tool in different collaborative environments (Sonderegger et al, 2013). Moreover, personality traits also play a key role in collaborative scenarios (Solimeno et al, 2008).…”
Section: Emotions and Personality In The Collaborationmentioning
confidence: 99%
“…The influence of mood feedback. Sonderegger et al (2013) offer experiences that examine the influence of mood feedback on different outcomes of teamwork in two different collaborative work environments. The authors present a new collaborative communication environment, using an avatar, which provides visual feedback of each team member's emotional state to support teamwork.…”
Section: Improved Qualities In Health and Support In Work Designmentioning
confidence: 99%